(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Our patients, whose care and cure is main objective of our profession, have many complaints and grievances against doctors and medical profession. When we try to analyze, most of the complaints fall into four categories. 1. Management issue: like too much wait in medical offices or in our outdoors and poor response of our front desk management crew that can range from unanswered phone calls to appointment issues to failure to provide necessary information – medical or non-medical.